IMPLEMENTASI GLOBAL LEADERSHIP COMPETENCY DI UPTD PUSKESMAS KUARO KABUPATEN PASER - Vieell Sidhatut Thoharoni Syaltout; La Ode Wahiyuddin; Muhammad Husni Arifin (Journal Publicuho, 2022)
This study aims to reveal how leadership is implemented based on the Global Leadership Competency Model at the Kuaro Health Center, Paser District. The method used in this study is a qualitative method with a case study approach, in order to understand and analyze in depth the competence of leaders at the Kuaro Health Center. Data collection techniques with interviews, observation and documentation. Data analysis was carried out interactively qualitatively. The results of the research show that first; the leaders at the Kuaro Health Center have not been able to create self-awareness and unstable emotions, second; the optimism and empathy of the leaders of the Kuaro Health Center are still far from good, third; Leaders are unable to create change where this is not found in achieving an attractive vision that is able to be realized by the leadership of the Puskesmas. The dominant argument of this research is that the application of global leadership competency is not only applicable based on cultural complexity where there are many supporting elements outside of cultural complexity. The scientific contribution of this article is to explain the global leadership competency model in a narrow organizational environment but with high cultural complexity